Cambiode la matriz productiva y su relación con el sector microempresarial artesanal del cantón Quevedo, periodo 2014-2017 - Muñoz Quisilay, Diana Mercedes (2015)
This thesis project was developed with the aim of developing the productive matrix for craft microenterprise sector Quevedo Canton, whose matrix includes key elements such as: Diversification and generation of value added in the production of goods, strategically replacing imports processed goods, and increase exports. It was established through market research and technical surveys and observation microenterprise sector requires massively institutional unionization as it currently makes up only 50% of the target universe, likewise, should strengthen training through Model Competency training designed in this proposal, helping to produce more godos and services in the shortest time possible and in the best quality foundation to achieve sustainable socio-economic development and promote productive activities in Pro of society and the Good Life of the Quevedeña society and industry influence. For this purpose methods, techniques and research tools that enabled a rapprochement with the totalizing reality under study were applied. The situational analysis established through a representative sample, which is required to insert urgent changes in the microenterprise sector; for which it is proposed to adopt the production model designed in this research and the….